Teachers’ Perception Toward Silent Way Method Used in EFL Classroom - Nihta V. F. Liando; Maria I. Poluan; Ignatius J. C. Tuerah (Universitas Muhammadiyah Enrekang, 2024)
Today's English learners are required to learn English independently and motivated because they cannot rely too much on their teachers to learn in the classroom. The present study was to seek how the teachers’ perception toward silent way method used in EFL classroom. Title: Teachers' Perceptions of the Silent Way Method in EFL Classrooms: A Qualitative Inquiry. This study investigates the perceptions of teachers regarding the utilization of the Silent Way method in English as a Foreign Language (EFL) classrooms. The Silent Way approach, characterized by its learner- centered, non-verbal communication techniques, has garnered attention for its potential to enhance language acquisition. Through a qualitative inquiry employing interviews, observations, and document analysis, this research explores teachers' experiences, challenges, and beliefs concerning the implementation of the Silent Way method. Findings offer insights into the effectiveness of this approach, its alignment with pedagogical principles, and implications for EFL instructional practices. Adopting quantitative methodological design and analyzing the data collected through questionnaires, it was revealed that (1) teachers’ perception toward the use of silent way in English class is really positive and helpful for teachers’ itself (2) the use SWM is really have many advantages, teachers are suggested to tried using this because by the students’ think it’s more challenging; as for learners, learners are encouraged to be independent in language learning through training activity in the classroom or with grouped learning activity outside the class with peers and merits the internet for good.